Canine megaesophagus secondary to acetylcholinesterase inhibitors (chumbinho) intoxication: an unusual presentation - Oaskis, Juliana Roberts; Machado, Sofia Munaldi; Cezana, Jórnie Mantovani; Andrade, Wanderson Lopes; Palácio, Bruna Batista; Andrade Júnior, Paulo Sérgio Cruz de; Amaral, Camila Barbosa (Medicina Veterinária, 2020)
Megaesophagus is a disease characterized by generalized esophageal dilatation, resulting from reduced or absent esophageal motility. It can be congenital or acquired and some common causes are persistent right aortic arch and myasthenia gravis. It can also be secondary to a variety of diseases, including intoxications. Although organophosphate poisoning is cited as a possible cause of megaesophagus, literature reports in dogs are rarely described. Such condition should have its importance emphasized, since poisoning by pesticides are relatively common in domestic animals and humans, whether accidently or intentionally. This study aimed to report the case of a dog which survived an episode of intentional pesticide poisoning and developed megaesophagus afterwards. The dog presented clinical signs of regurgitation around two weeks after surviving an intoxication episode. The diagnosis was based on clinical features and contrasted radiographic imaging (esophagography) using barium sulfate, which confirmed the diagnosis. Since no megaesophagus-related clinical signs were present before the intoxication episode, its relation to organic-phosphorus induced delayed neuropathy (OPIDN) was presumed. Unfortunately, the owner delayed seeking veterinary assistance and the dog’s condition deteriorated, despite therapeutic efforts, leading to death. Necropsy was not authorized. This case highlights the importance of monitoring canine patients which survived an intoxication episode and also draws attention to the illegal use of organophosphate compounds in Brazil and its impact in humans, domestic animals and wildlife.